Islamic Mobile Banking Adoption: An Extended UTAUT Perspective Integrating Electronic Service Quality and Perceived Cyber Security - Ach Yasin; Imamuddin Imamuddin; Ahmad Ajib Ridlwan; Sri Herianingrum (UPT Publikasi Ilmiah UNISBA, 2026)
Information technology has fundamentally transformed the economic sector, significantly accelerating the adoption of digital financial services, including mobile banking. In Indonesia, although mobile banking usage has been rising sharply, its adoption in Islamic banking remains relatively limited, with approximately 11.47 million users compared to 97.22 million in conventional banking. This disparity highlights a critical research gap. Given Indonesia’s leading position in the global Islamic finance Development index, it is imperative to investigate the factors influencing the adoption of Islamic mobile banking. Accordingly, this study aims to examine and analyse the determinants of intention to use Islamic mobile banking services. Data are collected from 302 respondents in Indonesia and analysed using partial least squares structural Equation modelling. This study finds that constructs within the UTAUT model, namely Performance Expectancy, Social Influence, and Facilitating Conditions, significantly influence Behavioural Intention to continue using Islamic mobile banking, albeit with small effect sizes. In contrast, Effort Expectancy shows no significant effect. The variables of e-Service Quality, Perceived Expected Benefits, and Perceived Cyber Security significantly affect Behavioural Intention. These findings provide empirical evidence on the key factors driving the continued use of Islamic mobile banking. The findings indicate that enhancing Perceived Expected Benefits is essential. Islamic banks prioritise their policies to ensure that all features are transparent and fully aligned with Sharia principles, optimise communication about the benefits of mobile banking, and strengthen their cybersecurity infrastructure to facilitate broader adoption within society.